Importance of psychotherapy for transgender children and adolescents: a literary analysis (Research, Society and Development, 2023)
A transgender person is someone who does not identify with their gender at birth. Such incongruity can occur from child hood in small actions noticed by parents or educators. The relationship between mental health and transgender children and adolescents is a subject that is little discussed, but which is extremely important for understanding the difficulties in order to minimize consequences. Thus, this systematic literature review proposes answer the following question: “What is the importance of psychotherapy for transgender children and adolescents?”. So, the PICO (Acromium for Pacient, Intervention, Comparision and Outcome) strategy was applied and the scientific production from 2016 to 2022 was analysed. It was found that the studies are limited, but the establishment of bonds between transgender patients and psychotherapists allows support in a moment of uncertainty in the lives of the family and children in transition and can be beneficial. It is also worth noting that aggravating factors such as prejudice and intolerance are installed in society even by social institutions, which increases social pressure and internal conflicts in young people who are no longer satisfied with their identity. Despite the lack of discussion on the subject and the low qualification of many professionals on how to deal with the target audience, it is possible to promote family benefits in a better understanding of the theme. Certainly, the article seeks to provide a broader approach to medical and psychotherapeutic aspects that are likely to be implemented and to mitigate the prejudice that society in general has about transgender youth.